Análise do comportamento mecânico da ligação entre madeira roliça por pino metálico - Silva, Pedro Henrique Shinohara da (2020)
With the increasing use of roundwood in engineering works such as bridges, rustic buildings, frames, decorative pérgolas, and others, there is a need to advance the mechanical behavior knowledge of the connections applied in this type of solution. With the purpose of improve the knowledge about the joints of wood pieces, this research aims to analyze the mechanical behavior of the connections between round pieces of wood with metal bars. Using NBR 7190 (ASSOCIAÇÃO BRASILEIRA DE NORMAS TÉCNICAS, 1997) as a normative basis, it is intended to create test pieces with roundwood connected by screws, performing the tests at two angles of the wood fibers in relation to the load applied, analyzing them for their mechanical resistance and rupture mechanisms. Despite of having higher load capacity compared to normal fiber angle connections assays, the results of parallel connections assays were more dispersed and had a higher number of unfinished assays. The most frequent rupture mode was the flexing of the metal bar on the internal piece of wood, observed in four tests. Among the 18 tests, seven were not completed due to failures in fixing the test pieces to the testing machine.